IDENTIFIKASI FAKTOR PENYEBAB KERETAKAN PADA PLATFORM MODULE (H-BEAM) MENGGUNAKAN METODE NDT (NON DESTRUCTIVE TEST) DI PT MULTI GUNUNG MAS BATAM - Anggia Arista; Rony Prasetyo (Universitas Putera Batam, 2018)
An Offshore platform module is used as fondation to support and sustain the weigt of all activities that accur on the module. The platform is a combination of a large H-Beam that incorporates to welding process. The vibration mechine and the process can lead to crack (fracture) at H-beam welding and will continue to propagate and be fatal. As a precaution to quality control tool need does not spoil the outcome of the H-beam are assemble by using of NDT (Non Destructive Test) method and ultrasonic techniques as cracking defect detection (crack) which occurs in the H-beam. The variables used are metal material cracks, material cracking factors and frequency of cracking factors. To analyze the cracking are using pareto chart and fishbone diagram. The relationship between the factors that cause disability to defects caused using chi squere calculation. The results of this study are that there are 4 factors that cause defects, namely the welding flame is too small, the welding flame is too large, the material is too thick and dirty in the welding area. The conclusion of this study requirement is material strenght rift in the welding H-beam process with the level of comparison between chi squere count 141,83 is greater than the chi squere table 21,66 and with degrees of free 9, and with the Contingency coefficient of 0,89 which indicates ther is a strong influence among the causes of the rift.